Analisis Pengaruh Dana Zakat Dalam Mengatasi Kemiskinan di Indonesia pada Tahun 2017-2021 - Irma Dinda Hanifah; Bayu Ardianto; Elendyar Meiningtiyas; Agus Eko Sujianto (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
Numerous nations, especially developing nations like Indonesia, frequently struggle with poverty. The goal of this study is to determine whether the use of zakat funds may help people get out of poverty. Utilizing quantitative techniques in this study. The research used annual data from zakat funds and poverty between 2017 and 2021. To ascertain if zakat funds have an impact on poverty in Indonesia, this study applies regression analysis through OLS (Ordinary Least Squares) analysis. The study's findings demonstrate that zakat funds have a favorable and considerable impact on poverty.